The relationship between form four students' beliefs and achievements in English / Wan Zainuddin Wan Hassan - Wan Hassan, Wan Zainuddin (2009)
This study focuses on the relationship between Form Four students' beliefs and achievements in English. Thus, it looks into three relevant issues: i) the beliefs held by students, particularly in rural areas, ii) the relationship between students' beliefs and their achievements in the language, and iii) aspects of beliefs which contribute significantly to the achievements. The beliefs encompass five main variables which are second language aptitude, the difficult in second language learning, the nature of second language learning, learning and communication strategies, and motivation. The Beliefs about Language Learning Inventory (BALLI) constructed by Horwitz (1983) was used to elicit the data. Besides, an interview schedule and an English language test are also utilized to find out the relationship between the two variables. 270 Form Four students were selected as the respondents of the study. The respondents were required to sit for the English test. The questionnaire was also administered to the respondents. However, merely 27 students were interviewed to support data yielded by the questionnaire. The findings of this study showed that all variables of BALLI affected students' achievements in English where, specifically, two main factors, i.e., the difficulty of second language learning and motivation significantly contribute to their achievements in the target language. Therefore, it is recommended that teachers concentrate more on these two variables to improve students' achievements in English as they are deemed important factors to their achievement in the target language.